Transobturator tape material detected in the bladder neck: a case report - Yavuz Güler; Akif Erbin; Burak Üçpınar (Journal of Medical Case Reports, 2019)
Abstract Introduction Stress urinary incontinence surgeries (transobturator tape and tension-free vaginal tape) are safely performed with success rates over 90%. The transobturator tape procedure attracted more attention due to the lack of major complications, such as intraabdominal organ and vascular injuries, related to the tension-free vaginal tape procedure. Although there are no major or mortality-related complications, more lower urinary complaints, especially vaginal erosion, are reported in transobturator tape surgery. Here we present a rare complication of transobturator tape surgery: the accidental placement of mesh material in the bladder neck. With this case report, we aimed to discuss the diagnosis and management of misplaced transobturator tape material. Case presentation A 38-year-old Caucasian woman who had stress urinary incontinence that had persisted for 6 years underwent transobturator tape surgery in a different clinic 2 years ago. Subsequently, she presented to our clinic with lower urinary tract complaints such as incontinence and dysuria. A physical examination was unremarkable besides total incontinence. A diagnostic cystoscopy was performed and sling material that crossed her bladder neck from 3 o’clock to 10 o’clock was identified. The misplaced transobturator tape material was cut endoscopically with an internal urethrotomy knife. Afterwards, a midurethral incision was made and mesh parts were removed bilaterally. After successful removal of the mesh material, a new transobturator tape was placed. Conclusions Even though transobturator tape surgery is a safe and effective procedure for stress urinary incontinence, certain complications can be encountered. Misplacement of the mesh material through the bladder neck is a rare complication and can be managed by successfully removing the mesh material and appropriately placing new transobturator tape material.